How to Resolve the Problem of Drago's Four Parameters in the Context of Molecular Interactions - Tran, Ho Nam; Michel, Buchmann (Journal of Applied Solution Chemistry and Modeling, 2019)
This study aims to provide a new thermodynamic method for determining the value of Drago's four interaction parameters, namely Ea, Eb, Ca, and Cb (kcal1/2 mol-1/2). The method is based on the following fundamental novelties: The values of the parameters Ea, Eb, Ca, and Cb are simultaneously determined for seven amphoteric substances. Thus, there are a total of 28 values to be determined, with each set consisting of seven substances. For the seven selected amphoteric substances, there are seven equations of the type: V∂2h / n = (Ea Eb + Ca Cb) Next, all possible 2-to-2 combinations of these seven substances are generated. For each 2-to-2 combination, one of the two is selected as a solute (2) and the other as a solvent (1), or vice versa. By measuring the mixing energy, ΔEmix (2.1), of these combinations, the 21 measurements available to extract the energy, ΔEint, of chemical bonds, according to the enclosed Buchmann paper: ΔEmix (2.1) = (Ea1 Eb2 + Ca1 Cb2) + (Ea2 Eb1 + Ca2 Cb1) Next, the seven equalities of the type V∂2h / nj = (Eaj Ebj + Caj Cbj) (kJ / mol) with j = 1,7 are put together with 21 equalities of the type ΔEint = (Eaj Ebj+1 + Caj Cbj+1) + (Eaj+1 Ebj + Caj+1 Cbj). This will generate a system comprising 28 equations for 28 unknown parameters. The resolution of this system will afford the 28 sought values of Drago's four parameters Ea, Eb, Ca, Cb for the seven selected substances.